Physiological and psychological variables among elite female athletes from three categories of sports and non-athletes - Aggarwala, Jyotsna; Garg, Rinku; Chatterjee, Subhra (International journal of health sciences, 2022)
Background: The aim of the study was to categorize various body composition, physiological and psychological variables among Indian elite female athletes participating in endurance sports (Group A, n= 22, age= 17.01±0.99 years), combat sports (Group B, n= 20, age= 19.15±3.63 years) and skill sports (Group C, n= 25, age= 18.80±2.21 years) and non- athletic control group (Group D, N= 23, years= 18.34±1.87 years). Methodology: Physical parameters included body fat percent, lean body mass, muscle content and total water content. Physiological parameters included time domain and frequency domain parameters of heart rate variability and maximal aerobic power (VO2 max) measured using Astrand protocol. Various psychological parameters were evaluated using Big Five Inventory and State-Trait Anxiety Inventory questionnaires. Results: Discriminant analysis revealed three significant functions (P<0.05) contributing 78.2%, 13.2% and 8.7% respectively to the model. After cross validation, the resulting equation correctly classified 68.3% of endurance, combat, skill athletes and control group. Total eighteen variables significantly (P<0.05) contributed to the discriminant analysis. The interpretation of the acquired discriminant functions was also based on examination of the structure coefficients greater than 0.30.